The Political Economy of the Unlawful Land Occupation in Post-1994 Cato Manor, Durban, South Africa - Yende, Nsizwazonke Ephraim (Commonwealth Youth and Development, 2024)
Socio-economic issues including the housing deficit, poverty, and unemployment have intensified unlawful land occupation in South Africa. This phenomenon is usually met with the police force deployed by municipalities to evict and demolish illegally constructed housing structures. The destruction of these structures is frequently met with resistance from the people, leading to clashes with the police that cause severe injuries and sometimes even death. Cato Manor in the eThekwini Metropolitan Municipality has not been spared from unlawful land occupations. This article explored the complexities associated with land occupation in post-1994 Cato Manor. It adopted a qualitative research approach and used Arnstein’s ladder of citizen participation to interpret the findings. Purposive and snowball sampling methods were adopted to recruit the 33 participants. Thematic analysis facilitated by NVivo Release 1.0 (NVivo 20) was used. The findings established multifaceted causes of unlawful land occupation in post-1994 Cato Manor. Land occupations are viewed as a form of boycott against the government’s inability to deliver housing and address past injustices emanating from spatial disparities. Such occupations resemble those which occurred in Cato Manor in the 1950s.